Greenium: Bentuk Keberpihakan Investor pada Pembangunan Berkelanjutan - Tita Nurvita; Noer Azam Achsani; Lukytawati Anggraeni; Tanti Novianti (Jurnal Akuntansi dan Governance, 2023)
Objectives. The purpose of this research is to compile a systematic literature review (SLR) regarding green bond research on the topic of greenium.Design/method/approach. The design of this research is a Literature Study. The data are collected from journals published from 2018 to 2022 and analyzed using the Protocol Search Appraisal Synthesis Analysis and Report (PSALSAR) method.Results/findings. The results showed that there are inconsistencies in the results where greenium is found in some studies and not found in other studies. In addition, there are different methods used to identify greenium. For further research on topics such as finding the determination of the emergence of greenium is still open. Theoretical contribution. This research provides additional theoretical contributions and new discussions regarding the valuation of financial assets, where apart from economic factors, non-economic factors also influence the valuation of financial assets, including investor taste.Practical contribution. This research contributes mainly to research on greenium because it found differences in investment motivation of green bond investors, so that it can be an input for further research and policies that can be taken for the development of green bonds. Limitations. This research only uses articles originating from Scopus Elsevier so that in future research it will expand the source of other articles from sources that are credible and reliable